MARINE PROTECT AREA (MPA) SEBAGAI STRATEGI EKONOMI PEMANFAATAN SUMBERDAYA KELAUTAN - Jardie Androkles Andaki (Fakultas Pertanian, Universitas Riau, 2010)
This study aims to explain the success of marine protected areas (MPAs) as a strategyfor economic utilization of marine resources. Method study through literature review aswell as some previous research related to the strategy of sustainable utilization ofmarine resources. From the study results conclude 1) Marine Protect Area (MPA) isdesigned for a number of reasons, including fisheries management, tourism promotion,and maintaining biodiversity; 2) MPA can provide added value not only economicbenefits to be gained, but also in the ecological benefits long term will also provideadditional economic benefits to the marine protected area; 3) In the area of protection,benefits not only to benefit the direct benefits from the utilization of its resources, butinclude broader benefits including social benefits from the presence of marine protectedareas; 4) The role of government in terms of coordination, cooperation and funding isneeded for the success of MPA, in addition to the use of MPAs as a potential area ofsustainable funding sources for sustainable management.